Occupational therapy students' experiences and perceptions of journal club participation. - Helgøy, Kjersti Velde; Bonsaksen, Tore; Mørk, Gry (Scandinavian Journal of Occupational Therapy, 2024)
Background: Journal clubs can be used as a learning activity for developing students' skills in critical appraisal and are perceived as suitable for increasing students' exposure to research methods. Aims/objectives: To explore how undergraduate occupational therapy students experienced journal club and how they perceived their learning outcomes from participating in this learning activity. Materials and methods: A mixed methods study comprised of a survey followed by two focus groups was conducted. Seventeen occupational therapy students completed the survey, four of whom also participated in a total of two focus groups. Results: The participants perceived journal clubs as suitable and they suggested that emphasis on this learning activity be increased. Across the two focus groups, four integrated themes were identified: 'organisational prerequisites'; 'potential for learning'; 'learning barriers'; and 'journal club as an integrated learning activity'. Conclusions and significance: Journal clubs were described as having the potential for increasing students' learning regarding research methods, promoting skills in reading and critically reviewing research articles and having relevance for professional practice. Some barriers were identified, and changes are suggested for future educational practice.